\(-8+8y^2-6y^4+y^6\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 10 2020

\(-8+8y^2-6y^4+y^6\)

\(=y^6-6y^4+12y^2-8-4y^2\)

\(=y^6-3.2.\left(y^2\right)^2+3.y^2.2^2-2^3-4y^2\)

\(=\left(y^2-2\right)^3-\left(2y\right)^2\)

10 tháng 10 2020

Sắp xếp lại ta được

y6 - 6y4 + 8y2 - 8

= ( y2 )3 - 3.( y2 )2.2 + 3.y2.22 - 23 - 4y2

= ( y2 - 2 )3 - 4y2

10 tháng 10 2020

bằng -16

\(1.\)

\(4x^2-12x+9\)

\(=\left(2x\right)^2-12x+3^2=\left(2x-3\right)^2\)

\(2.\)

\(7x^2-7xy-5x+5y\)

\(=7x\left(x-y\right)-5\left(x-y\right)\)

\(\left(7x-5\right)\left(x-y\right)\)

\(3.\)

\(x^3-9x\)

\(=x\left(x^2-9\right)\)

\(=x\left(x-3\right)\left(x+3\right)\)

\(4.\)

\(5x\left(x-y\right)-15\left(x-y\right)\)

\(=\left(5x-15\right)\left(x-y\right)\)

\(=5\left(x-3\right)\left(x-y\right)\)

\(5.\)

\(2x^2+x\)

\(=2x\left(x+1\right)\)

\(6.\)

\(x^3+27\)

\(=\left(x+3\right)\left(x^2-3x+9\right)\)

\(7.\)

\(2x^2-4xy+2y^2-32\)

\(=2\left(x^2-2xy+y^2-16\right)\)

\(=2\left[\left(x^2-2xy+y^2\right)-16\right]\)

\(=2\left[\left(x-y\right)^2-4^2\right]\)

\(=2\left(x-y+4\right)\left(x-y-4\right)\)

\(8.\)

\(x^3-4x-3x^2+12\)

\(=\left(x-3\right)\left(x-2\right)\left(x+2\right)\)

\(9.\)

\(2x+2y+x^2-y^2\)

\(=2\left(x+y\right)+\left(x-y\right)\left(x+y\right)\)

\(=\left(x+y\right)\left(x-y+2\right)\)

\(10.\)

\(x^2y-2xy+y\)

\(=y\left(x^2-2x+1\right)\)

\(=y\left(x-1\right)^2\)

\(11.\)

\(y^2+2y\)

\(=y\left(y+2\right)\)

\(12.\)

\(y^2-x^2-6y-6x\)

\(=\left(y-x\right)\left(y+x\right)-6\left(y+x\right)\)

\(=\left(y+x\right)\left(y-x-6\right)\)

\(13.\)

\(x^3-3x\)

\(=x\left(x^2-3\right)\)

\(=x\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)\)

\(14.\)

\(2x-xy+2z-yz\)

\(=x\left(2-y\right)+z\left(2-y\right)\)

\(=\left(2-y\right)\left(x+z\right)\)

Xong

4 tháng 7 2018

cảm ơn nhiều lắm

6 tháng 10 2017

\(x^3y^3+x^2y^2+4=x^2y^2\left(xy+1+4\right)\)

10 tháng 9 2019

1) 

a) \(2x^2-12x+18+2xy-6y\)

\(=2x^2-6x-6x+18+2xy-6y\)

\(=\left(2xy+2x^2-6x\right)-\left(6y+6x-18\right)\)

\(=x\left(2y+2x-6\right)-3\left(2y+2x-6\right)\)

\(=\left(x-3\right)\left(2y+2x-6\right)\)

\(=2\left(x-3\right)\left(y+x-3\right)\)

b) \(x^2+4x-4y^2+8y\)

\(=x^2+4x-4y^2+8y+2xy-2xy\)

\(=\left(-4y^2+2xy+8y\right)+\left(-2xy+x^2+4x\right)\)

\(=2y\left(-2y+x+4\right)+x\left(-2y+x+4\right)\)

\(=\left(2y+x\right)\left(-2y+x+4\right)\)

2)  \(5x^3-3x^2+10x-6=0\)

\(\Leftrightarrow x^2\left(5x-3\right)+2\left(5x-3\right)=0\Leftrightarrow\left(x^2+2\right)\left(5x-3\right)=0\)

Mà \(x^2+2>0\Rightarrow5x-3=0\Rightarrow x=\frac{3}{5}\)

\(x^2+y^2-2x+4y+5=0\)

\(\Leftrightarrow x^2+y^2-2x+4y+4+1=0\)

\(\Leftrightarrow\left(x^2-2x+1\right)+\left(y^2+4y+4\right)=0\)

\(\Leftrightarrow\left(x-1\right)^2+\left(y+2\right)^2=0\)

\(\Leftrightarrow\hept{\begin{cases}x-1=0\\y+2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=1\\y=-2\end{cases}}\)

3)\(P\left(x\right)=x^2+y^2-2x+6y+12\)

\(P\left(x\right)=x^2+y^2-2x+6y+1+9+2\)

\(=\left(x^2-2x+1\right)+\left(y^2+6y+9\right)+2\)

\(=\left(x-1\right)^2+\left(y+3\right)^2+2\ge2\)

Vậy \(P\left(x\right)_{min}=2\Leftrightarrow\hept{\begin{cases}x-1=0\\y+3=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=1\\y=-3\end{cases}}\)

Bài làm

a) 2x2 - 12x + 18 + 2xy - 6y

= 2x2 - 6x - 6x + 18 + 2xy - 6y 

= ( 2xy + 2x2 - 6x ) - ( 6y + 6x - 18 )

= 2x( y + x - 3 ) - 6( y + x - 3 )

= ( 2x - 6 ) ( y + x - 3 )

# Học tốt #